A Study on Customers' Attitude towards Online Shopping - An Indian Perspective - Banerjee, Neelotpaul; Dutta, Anindya; Dasgupta, Tanmoy (Indian Journal of Marketing, 2010)
Since its inception, internet has become a popular marketing channel. Most companies now view the internet as an attractive medium to reach out to the customers. Marketers are investing substantial resources in the online marketing accompanied by rapidly increasing use of the internet by the customers. Online shopping is becoming a widely accepted way to purchase different goods and services. Customers buying intention, offline or online, is highly influenced by their attitude. Understanding customers' attitude is extremely important in marketing practices as attitude projects an actual behaviour. A better understanding of customers' attitude will help the online marketers to develop their strategies to satisfy online customers. This paper discusses the Indian customers' attitude toward online shopping. The analysis is based on a survey of 316 internet users in India. The study reveals that the availability of extensive and current information, monthly family income, and experience of using internet are the important factors influencing Indian customers' attitude toward online shopping. The results also indicate that customers' concern about online security is the most important reason for customers not engaging in online shopping.